M. Hulot's holiday - Clément, René 1913-1996 (Criterion Coll., 2001)
Tati portrays the endearingly eccentric character, Hulot, whose presence at a very proper French seaside resort provokes one outrageous catastrophe after another.
Orig.: F 1953. - Sprache: Franz. - Untertitel: Engl. - Enth. außerdem Réné Clément's Kurzfilm "Soigne ton gauche"
Keywords: Motion pictures, French; Seaside resorts -- Drama; Vacations -- Drama; Comedy films; Foreign films